Climate-Sensitive Diseases and Community Vulnerability in Coastal Indonesia: A Systematic Review with Narrative Synthesis - Reza Indra Wiguna; Lia Arian Apriani; Maulin Halimatunnisa; Mustika Ayu Lestari; Edy Surya Pratama (Poltekkes Kemenkes Surabaya, 2026)
Climate change is increasingly exacerbating health risks in tropical regions, particularly in archipelagic nations such as Indonesia. This study aims to systematically identify and synthesize scientific evidence on climate-sensitive diseases and community vulnerability in coastal Indonesia. A systematic review with narrative synthesis was conducted across four databases (PubMed, Scopus, ScienceDirect, and Google Scholar). The search was performed on 15 June 2025, covering studies published between 2013–2024. Of the 263 records identified, 20 studies met the eligibility criteria, consisting of 12 observational studies, 5 modelling studies, and 3 review or mixed-method papers. The findings indicate consistent associations between rising temperatures, shifting rainfall patterns, flooding, drought, and sea-level rise with increased incidence of dengue, malaria, diarrhea, filariasis, and climate-related mental health outcomes. These climate-sensitive risks are amplified by structural vulnerabilities, including inadequate sanitation, high population density, dependence on climate-sensitive livelihoods, and limited access to healthcare in coastal and remote areas. Most included studies originated from Indonesia and Southeast Asia, underscoring strong contextual relevance. The synthesis highlights that fragmented, sectoral approaches remain insufficient in addressing health impacts of climate change. Integrated strategies—such as climate-informed disease surveillance, community-based early warning systems, and strengthened cross-sectoral coordination—are urgently needed to enhance adaptive capacity. This review is limited by the absence of quantitative meta-analysis and the geographic focus on Indonesia. Future studies should employ longitudinal designs, higher-resolution spatial climate data, and interdisciplinary approaches to support more robust climate-health adaptation strategies.